Technological Revolution, Evolution and New Dependencies: what's new about ict4d? - Kleine, Dorothea; Unwin, Tim (Third World Quarterly, 2009)
This paper provides an overview of recent developments in the use of information and communication technologies for development, and argues that, while they do indeed offer new potential for resolving some of the classic dilemmas of development policy and practice, insufficient attention has yet been paid to the lessons that can be learnt from previous information and communication initiatives.